2014
DOI: 10.1055/s-0034-1375675
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Diabetes Mellitus (CoDiM) in Germany, Direct Per-capita Costs of Managing Hyperglycaemia and Diabetes Complications in 2010 Compared to 2001

Abstract: Cost for diabetes is largely caused by management of complications. It is important to prevent complications by consequent management of diabetes as well as by primary prevention of its onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 3 publications
4
40
1
7
Order By: Relevance
“…The Costs of Diabetes Mellitus (CoDiM) study, the largest claims data-based study, indicated that in 2010 direct medical costs for patients with and without diabetes were €5084 and €2693, respectively. 36 Whereas the absolute mean costs in our study were substantially lower (€3352 vs €1849), the cost ratio between patients with and without diabetes was quite comparable to that of the CoDiM study (1.8 in this study vs 1.9 in CoDiM). Several reasons might have contributed to these differences in total mean costs for diabetes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The Costs of Diabetes Mellitus (CoDiM) study, the largest claims data-based study, indicated that in 2010 direct medical costs for patients with and without diabetes were €5084 and €2693, respectively. 36 Whereas the absolute mean costs in our study were substantially lower (€3352 vs €1849), the cost ratio between patients with and without diabetes was quite comparable to that of the CoDiM study (1.8 in this study vs 1.9 in CoDiM). Several reasons might have contributed to these differences in total mean costs for diabetes.…”
Section: Discussionsupporting
confidence: 68%
“…The former finding confirms results from previous studies which also found that inpatient care and medication were the biggest cost drivers. 7 12 13 39 The latter finding is also supported by data from the CoDiM study which provided a cost ratio of about 3.1 for patients with diabetes with stroke and about 2.6 for patients with myocardial infarction compared with those without diabetes, 36 indicating that a large share of the costs for diabetes is attributable to the treatment of diabetes-related complications. 20 24 We also observed that the type of treatment had a strong effect on direct costs.…”
Section: Discussionmentioning
confidence: 78%
“…19 Finally, the total cost of antihyperglycemic treatments was lower in this work (€498) than in a study conducted in 2010 (€633). 20 This slight discrepancy between the findings of the 2 studies may be due to annual variations in the cost of antihyperglycemic drugs in Germany but may also be due to the difference in study methods.…”
Section: Discussionmentioning
confidence: 98%
“…29,30 The unadjusted mean total annual treatment costs for diabetes observed in the present study are in line with recent descriptive health economic studies in Germany. 31,32 Based on nationwide data from a large statutory health insurance (AOK PLUS), annual absolute costs were estimated for different subgroups of type 2 diabetes patients stratified by glycemic and blood pressure control and comorbidity. 31 A direct comparison with the present study, which included patients with newly onset insulin treatment, is not possible.…”
Section: Discussionmentioning
confidence: 99%